The impact of a multidisciplinary care package for vaccination in needle phobic children: An observational study. (26th February 2022) - Doyle, Rebecca; Donaldson, Alex; Philips, Leanne; Nelson, Laurelle; Clark, Julia E.; Wen, Sophie Chien‐Hui
Abstract : Aims: Children with severe needle phobia find vaccination extremely distressing and can remain unvaccinated, which puts them at an increased risk of contracting and transmitting vaccine preventable disease. Referral to a specialist or hospital service may occur when they cannot be safely vaccinated in the community, but engagement of allied health services can be inconsistent. The aim of the study was to assess the impact of a multidisciplinary, consumer‐oriented model of care on vaccinations for needle phobic children. Methods: Needle phobic children aged between 6 and 16 years attended multidisciplinary consultation, as part of a care package, to assess previous experiences and determine the level of intervention that was required to support vaccination. A multidisciplinary case meeting followed this appointment and an individualised plan formulated for each patient. The main outcome of the project was rate of successful vaccination. Results: The care package resulted in a successful vaccination rate of 83% ( n  = 20) with 69 vaccines administered across three clinics. Of those successful, 90% required multiple injections per visit. The majority of patients indicated moderate to high level of anxiety. Supportive care was escalated and de‐escalated as tolerated. Conclusions: Results demonstrate the diversity of patients presenting with needle phobia and indicate an individualised, collaborative approach is preferable to a 'one size fits all' model of care. The study highlights a need for the development of guidelines that streamline the assessment and individualisation of procedural anxiety plans to meet patient needs and embed these processes into standard care.